Effect of alternate day collection on semen quality of Asian elephants (Elephas maximus) with poor initial fresh semen quality - P. Imrat (2018)
In captivity, male Asian elephants often yield poor quality semen after transrectal manually assisted semen collection; however, the reasons for the disappointing semen quality are not clear. Here we test the hypothesis that accumulation of senescent spermatozoa is a contributory factor, and that semen quality can therefore be improved by more frequent ejaculation. To this end we investigated the effect of collecting semen five times on alternate days, after a long period of sexual rest, on semen quality in Asian elephants known to deliver poor semen during infrequent single collections. All eight bulls initially displayed a high incidence of detached sperm heads and low percentages of motile (close to 0%) spermatozoa. After semen collection on alternate days, the percentages of detached sperm heads, and head and mid-piece abnormalities, were reduced significantly (p < . 0.05). In particular, one bull showed markedly improved sperm motility (increased from 0% to 60%) and membrane integrity (increased from 5% to 75%). In addition, advancing age significantly (p < . 0.01) correlated with lower percentages of sperm with intact membranes and a higher frequency of detached sperm heads. In contrast to sperm accumulation problems in other species, a small ampullary diameter correlated significantly (p < . 0.05) with reduced semen quality. © 2014 Elsevier B.V.